Convergent ablation for persistent atrial fibrillation: outcomes from a single-centre real-world experience. (8th November 2022) - Mannakkara, Nilanka N; Porter, Bradley; Child, Nicholas; Sidhu, Baldeep S; Mehta, Vishal S; Elliott, Mark K; Gould, Justin; Ahmed, Shahada; Razavi, Reza; Rinaldi, Christopher A; Blauth, Christopher; Gill, Jaswinder S
Abstract: OBJECTIVES: Atrial fibrillation (AF) is common and can cause significant morbidity and detriment to quality of life. Success rates for conventional catheter ablation are suboptimal in persistent AF (PsAF), especially when longstanding. Convergent hybrid ablation combines endoscopic surgical epicardial and endocardial catheter ablation. It offers promise in treating PsAF. We aimed to evaluate outcomes at our centre following convergent ablation. METHODS: We conducted an observational study of patients undergoing ablation from 2012 to 2019 at a London cardiac centre. Sixty-seven patients underwent convergent ablation entailing epicardial ablation, mostly via sub-xiphoid access, followed by endocardial left atrial catheter ablation. Baseline and follow-up data were obtained retrospectively from clinical records. Primary outcome was freedom from AF on/off anti-arrhythmic drugs after 12-month follow-up. Secondary outcomes included freedom from AF over the entire follow-up, freedom from anti-arrhythmic drugs, freedom from atrial arrhythmias, symptom status, repeat ablation and complications. RESULTS: At baseline, 80.6% had PsAF >1 year (80.6%), 49.3% had body mass index >30 kg/m 2 at baseline and 19.4% had left ventricular ejection fraction of 40% or less. The median follow-up was 2.3 (1.4–3.7) years. Freedom from AF recurrence was 81.3% at 1 year and 61.5% over overall follow-up. Eleven patients (16.4%) required redo AF ablation. Prolonged AF duration was associated with increased recurrence at 12 months and duration >5 years with a shorter time to recurrence on Kaplan–Meier analysis, but this and other factors did not significantly impact the AF recurrence during the overall follow-up period. CONCLUSIONS: Convergent ablation had good 1-year and overall success rates for treating PsAF. Our results in a diverse, real-world population support the potential of convergent ablation in patients with challenging to treat PsAF. Abstract : Atrial fibrillation (AF) is the commonest arrhythmia encountered in clinical practice, affecting 33.5 million people globally, with an increasing worldwide disease burden [1–3].